Pengaruh Pengungkapan Tanggung Jawab Sosial Terhadap Penghindaran Pajak dan Peran Asuransi - Eko Budi Santoso (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
Corporate Social Responsibility (CSR) has been raised as firms strategic issue in developing countries such as Indonesia. Although the disclosure of social responsibility is still voluntary, many firms are starting to publicize their CSR activities and even provide assurance to get appreciation as socially responsible firms. However, several socially responsible firms have been engaged in tax scandals, raising questions of whether CSR disclosure is used to hide firm fraud or as a reflection of a real socially responsible firm. This study investigates the effect of CSR disclosure and tax avoidance and the role of sustainability reporting assurance to that association. Using Indonesian go public firms published CSR report as a sample, the empirical result shows that CSR disclosure positively effect tax avoidance. Furthermore, results also indicate sustainability reporting assurance moderates the association. The findings indicate that stakeholders should carefully examine firms with active CSR disclosure before labeling it as socially responsible firms.